2019
DOI: 10.1021/acs.joc.9b02541
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ring-Fused, N-Substituted 4-Quinolinones Using pKa-Guided, Base-Promoted Annulations with Isatoic Anhydrides: Total Synthesis of Penicinotam

Abstract: An anionic annulation strategy employing isatoic anhydrides and a wide assortment of enolizable partners was developed to afford over 80 novel ring-fused, N-substituted 4-quinolinones, an underrepresented privileged template. Multiple factors governing the efficiency of the transformation were determined, resulting in a reliable and tunable synthetic platform applicable for a broad range of substrates with variable deprotonation susceptibility, such as tetramic and tetronic acids, cyclic 1,3-diketones, and cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Taking into account the chemical structure of ISA, it is already known that the heterocyclic ring is considered the most reactive part of the molecule, being the carbonyl group attached to the aromatic ring, the most electrophilic group within the structure; thus, the observed reactivity involves a nucleophilic attack to the carbonyl group. [7,28,29] In addition, the nitrogen atom is expected to be either alkylated or compromised with the adjacent carbonyl group by sharing the lone pair of electrons yielding the observed carbamate-like reactivity which characterizes ISA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the chemical structure of ISA, it is already known that the heterocyclic ring is considered the most reactive part of the molecule, being the carbonyl group attached to the aromatic ring, the most electrophilic group within the structure; thus, the observed reactivity involves a nucleophilic attack to the carbonyl group. [7,28,29] In addition, the nitrogen atom is expected to be either alkylated or compromised with the adjacent carbonyl group by sharing the lone pair of electrons yielding the observed carbamate-like reactivity which characterizes ISA.…”
Section: Resultsmentioning
confidence: 99%
“…[2] Thus, some protocols with palladium catalysed process are available for the synthesis of this important intermediary. [3] Recently, ISA has gained importance as synthetic precursor of known pharmacological agents; its reactivity, characterized by decar-bonylative and ring opening reactions, has been successfully applied in the synthesis of quinazolin-4(3H)-ones, [4] quinazoline benzamides, [5] anilines, [6] and quinolones, [7] in a wide collection of new and outstanding synthetic methodologies. Hence the relevance of characterizing the reactivity of ISA, which offers the possibility to contribute to the design of improved and versatile synthetic methodologies and, to the best of our knowledge, it has not been yet described.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the importance of 4-quinolones as potential drugs and biological probes, it is not surprising that the development of methods for their synthesis is a very active area of research. Recent contributions to the synthesis of 4-quinolones made use of phosphine-mediated redox cyclization of 1-(2-nitroaryl)prop-2-ynones [39], palladium-catalyzed carbonylative cyclization of 2-bromonitrobenzenes and alkynes [40], TsCl-mediated domino reaction of chromone-3-carboxaldehydes and amines [41], Pd-catalyzed redox-neutral C-N coupling reaction of iminoquinones with electron-deficient alkenes [42], NH 3 insertion into o-haloarylynones [43], gold(III)-catalyzed azide-yne cyclization [44], Michael/Truce-Smiles rearrangement cascade [45], and base-promoted annulations with isatoic anhydrides [46]. Many other contributions in this field up to 2019 have been extensively reviewed [47][48][49], with special attention to the total synthesis and functional analysis of 2-alkyl-4-quinolones as microbial signaling molecules [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…Alkylation was completed in 24 h with an improved yield of 70–87% . Diisopropylethylamine (DIPEA) was also used for the formation of N -benzylated isatoic anhydride. , …”
Section: Introductionmentioning
confidence: 99%
“…5 Diisopropylethylamine (DIPEA) was also used for the formation of N-benzylated isatoic anhydride. 1,17 In 1997, Coppola reported that the alkylation of Nsubstituted isatoic anhydride can be easily done with sodium hydride/potassium carbonate bases followed by the addition of an alkylating agent. However, direct substitution on nitrogen with an aryl moiety is not possible.…”
Section: ■ Introductionmentioning
confidence: 99%